Culture and Museums in the Winds of Change: The Need for Cultural Indicators - Worts, Douglas (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2011)
How individuals live their lives, within the context of personal and collective values, expresses their living culture. Societies may be made up of people with different ethnocultural backgrounds, socio-economic profiles or spiritual orientations, but they share certain common cultural frameworks (e.g., democratic governance, rules of law, conventions of business, principles of equity for all, etc.) of what is increasingly a globalized, pluralized, and urbanized present. Culture is often thought of as either the historical traditions of a group, or else as certain types of activities (e.g., dance, theatre, celebrations, rituals, etc.) and objects (e.g., art, artifacts, clothing, etc.). Meanwhile, cultural organizations are characterized as specialized places of expertise that provide selected kinds of experiences and services to the public – normally available for consumption during leisure time. This article argues that the heart of living culture is to be found not in specialized types of objects, leisure-time experiences, ethnocultural traditions, or cultural organizations but, rather, in its processes of human adaptation in a changing world. The author uses the lens of culture to examine how humanity understands and attempts to manage change within its sphere of influence. How can we best measure the cultural well-being of our societies, our organizations, and ourselves? The overarching notion of global/local sustainability provides the grounding point for considering how best to foster a 'culture of sustainability'.